First-line tremelimumab plus durvalumab and chemotherapy versus chemotherapy alone for metastatic non-small cell lung cancer: a cost-effectiveness analysis in the United States - Liu, Wenjie; Huo, Gengwei; Chen, Peng (Frontiers in Pharmacology, 2023)
In the open-label phase III POSEIDON randomized clinical trial (RCT), a limited course of tremelimumab plus durvalumab and chemotherapy (T + D + CT) indicated in the first-line treatment of metastatic non-small cell lung cancer (mNSCLC), progression-free survival (PFS), and overall survival (OS) were substantially improved without significant additional tolerance burden compared to chemotherapy (CT). However, given the high cost of T + D + CT, its value needs to be evaluated in terms of both potency and cost.To evaluate the cost-effectiveness of T + D + CT versus CT in individuals with previously untreated mNSCLC from a U.S. payer perspective.A three-state Markov model was adopted to weigh the lifetime costs and effectiveness of T + D + CT versus CT for the treatment of first-line mNSCLC, according to the results of the POSEIDON phase III RCT involving 675 individuals with mNSCLC. Individuals were simulated to undergo either T + D + CT for up to four 21-day cycles, followed by durvalumab once every 4 weeks until disease progression or unacceptable toxic effects and one additional tremelimumab dose, or CT for up to six 21-day cycles (with or without pemetrexed maintenance; all groups) in the analysis.Lifetime costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) were evaluated with a willingness-to-pay (WTP) threshold of 100,000 to 150,000 per QALY. The uncertainty of the model was investigated using univariate and probabilistic sensitivity analysis.